Pembangunan Hukum Dalam Menciptakan Masyarakat Yang Anti Korupsi - Pasaribu, Kondios Meidarlin (Indra Institute Research & Publication, 2024)
Corruption has consequences that are very dangerous for human life, both aspects of social, political, bureaucratic, economic, and individual life. The danger of corruption to life is likened to corruption is like cancer in the blood, so the owner of the body must always do continuous